ADMINISTRATIVE WORKSHOP DESIGN APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 MEKAR JAYA - Zulfa Husnul Maab; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2005)
Discuss the information system at the Administration on workshops Mekar Jayawhich recorded the activities of service by cash payment, it is drawn through the dataflow diagram, entity relasitianship diagrams, normalization, which can then be madea computerized information system to process transaction data better than dengawnprocessing data manually. So that the resulting information more quickly andaccurately.